The prevalence and factors associated with undiagnosed dysglycaemia in established rheumatoid arthritis / Nur ‘Aini Eddy Warman - Eddy Warman, Nur ‘Aini (2017)
Background: Rheumatoid arthritis is a chronic inflammatory disease with an increased risk of diabetes and insulin resistance. Aims: To determine the prevalence of undiagnosed dysglycaemia and investigate the factors associated with it in patients with established RA. Methods: This was a cross-sectional study conducted in a rheumatology centre. One hundred fifty five consecutive patients were recruited. The inclusion criteria were patients with established RA, age > 30 years. Patients with diabetes or pre-diabetes were excluded. Demographic details, clinical data on RA and anthropometric measurements were obtained. Laboratory investigations performed included erythrocyte sedimentation rate, C-reactive protein, intracellular adhesion molecule (ICAM), lipid profile and plasma glucose. A 75goral glucose tolerance test was performed to determine dysglycaemia. Comparison of variables were done between two groups; dysglycaemia and normoglycaemia. Results: The mean age of patients was 57.2±8.1 years and majority (87.7%) were female. 35.5% (n=155) had dysglycaemia. Apart from ever smoker, there were no significant differences observed in age, gender and disease duration between the groups. Although RA disease activity and the average dose of corticosteroid used within six months were higher in dysglycaemia group, the differences were not statistically significant. Significant differences were observed in waist circumferences, weight, systolic and diastolic blood pressure, high-density lipoprotein, triglycerides and ICAM levels but after multivariate analysis, the predictors of dysglycaemia were ever smoker and high triglyceride level. Conclusion: One-third of our patients had dysglycaemia and they were heavier, larger waist circumference, higher blood pressure and LDL-c, and lower HDL-c. Predictors of dysglycaemia in established RA aged ≥30 years were ever smoker (OR 4.28) and high triglyceride level (OR 3.29).